2016
DOI: 10.4236/ajps.2016.712157
|View full text |Cite
|
Sign up to set email alerts
|

Peoples’ Perception and Conservation of <i>Dactylorhiza hatagirea</i> (D. Don) Soó in Manaslu Conservation Area, Central Nepal

Abstract: The present study analyzes the information and perception of the local community of Samagaun VDC, Manaslu Conservation Area Project (MCAP) regarding Dactylorhiza hatagirea (D. Don) Soó (Orchidaceae). We assessed the local peoples' perception on its population status, its availability, factors causing its decline and management practices of this terrestrial orchids. A pre-designed questionnaire was used to gather information targeting the age group between 25 and 60 years (n = 75, 45 male and 30 female). Most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In Nepal, only a few studies have focused on the abundance, density, and conservation of D. hatagirea [ 46 , 47 , 58 ], and only one on suitable habitat modelling [ 59 ]. Possible effects of climate change on its distribution have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, only a few studies have focused on the abundance, density, and conservation of D. hatagirea [ 46 , 47 , 58 ], and only one on suitable habitat modelling [ 59 ]. Possible effects of climate change on its distribution have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a density of 2.18 individuals per•m 2 with frequency and abundance of 81.81% and 2.67 individuals per•m 2 , respectively, indicating that the species is threatened in the study area. Pandey et al (2016) also reported overgrazing of domestic animals, over-harvesting, and lack of awareness among the local community as significant causes of D. hatagirea decline in then Samagaun Village Development Committee (VDC) of Manaslu Conservation Area (MCA). Khadka et al, (2016) reported a density of 0.276 per m 2 of D. hatagirea in Lete VDC of Mustang District, indicating the functional ecological status but unsatisfactory plant diversity, which suggested for immediate necessary actions for the conservation of the diversity in the study area.…”
Section: Distributionmentioning
confidence: 99%